Cytochrome P450 1A2 activity and incidence of thyroid disease and cancer after chronic or acute exposure to dioxins. Issue 3 (8th November 2019) - Samer, Caroline Flora; Gloor, Yvonne; Rollason, Victoria; Guessous, Idris; Doffey‐Lazeyras, Fabienne; Saurat, Jean‐Hilaire; Sorg, Olivier; Desmeules, Jules; Daali, Youssef
Abstract: Background: Dioxin (2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin; TCDD) is the most toxic congener of a family of structurally and mechanistically related persistent organic pollutants whose effects are mediated through the aryl hydrocarbon receptor (AhR). Induction of CYP1A1/2 by TCDD through the AhR depends on the magnitude and the duration of exposure. We aimed to assess CYP1A2 activity after acute and chronic exposure to TCDD. The Maincy cohort is a sample population from Melun in the Val‐de‐Seine region in France that lived for at least 5 years close to a waste incinerator emitting polluted vapours (1974‐2002) with high concentrations of dioxins (up to 2000 times the maximal recommended values). Acute exposure to TCDD (Viktor Yushchenko) has been described elsewhere by Sorg et al (Toxicol. Sci. 2012; 125:310‐317). Both are rare cases of well‐identified source of chronic and acute exposure to TCDD. Methods: All subjects underwent a full medical history and physical examination and had a cutaneous examination, and a retro‐auricular skin biopsy was taken. A questionnaire was designed and used regarding demographic, personal, environmental and occupational characteristics. CYP1A2 activity was assessed 2 hours after the ingestion of a drink containing caffeine through measurement of the metabolic ratio of paraxanthine (17X) over caffeine (137X) by LC‐MS/MS or LC‐UV. CYP1A1 expression in skin biopsies was determined by immunohistochemical analysis. Results: Forty‐seven exposed subjects (age 11‐78) and 31 controls were included in the study. Eleven exposed subjects had a history of thyroid disease (23.4%), and 7 (14.8%) had a cancer vs none and 1, respectively, in controls. Nodular skin lesions were found in 13 exposed subjects (27.7%) vs none in controls. Mean CYP1A2 activity of the exposed population was modestly elevated as compared to controls (17X/137X metabolic ratio of 0.475 vs 0.374, P = .051). CYP1A2 was, however, induced (17X/137X, metabolic ratio >0.5) in 27.6% of the exposed cases vs 6.4% of the controls. In contrast, acute dioxin exposure was associated with a strong induction (mean 17X/137X, metabolic ratio of 1.9) still present 29 months after the acute exposure. CYP1A1 was expressed in 59.6% of the skin biopsies (highly expressed in 31.9%) of the Maincy cohort. No correlation between CYP1A2 activity, CYP1A1 expression and clinical manifestations (thyroid disease, cancer, skin lesions) could be demonstrated. Conclusion: Higher frequencies of dysthyroidism and cancer were detected in the population exposed chronically to dioxins from a waste incinerator. CYP1A2 was induced in 27.6% of the exposed population, while the magnitude of induction was fourfold higher after acute exposure in the case of Yushchenko.